The demography of the Hispanic population : selected essays - Verdugo, Richard R. (Hispanic population in the United States (Charlotte, N.C.), 2012)
The Hispanic population has dramatically grown since the middle of the 20th Century. Demographers predict that by the year 2050, one in three Americans will of Hispanic origin. But the Hispanic population is not a homogeneous group; it varies by race and ethnicity, culture, economic status, education, and other important factors.The purpose of the present volume is to provide information on selected topics regarding the growth, distribution, and size of the Hispanic population. The volume brings together an eclectic set of six research papers. The first four examine traditional demographic topics: population growth, mortality, and immigration. The last two address topics that are not often examined among Hispanics: Hispanic Baby Boomers, and an interesting study on self identification among Hispanics using vital events data and census data.